PRAKTIK MENJUAL BAJU JAHITAN YANG DI TINGGAL PEMILIKNYA DI PENJAHIT PARIS CUKIR JOMBANG MENURUT HUKUM EKONOMI SYARI’AH - Rosandi Firmawan; Norma Fitria (CV. KAMPUS AKADEMIK PUBLISING, 2025)
. This study examines the practice of buying and selling sewn clothes left by their owners for a long period of time at the Paris, Cukir, Jombang tailoring business. This phenomenon arises as a form of microeconomic problems in the service sector, where customers who have ordered and sewn clothes do not return to pick up or pay for their sewing results. This causes losses for tailors who have allocated time, energy, and production costs, but do not obtain the rights to their services. The tailor then takes steps to sell the clothes to other parties to minimize losses. This study aims to determine the practice of buying and selling sewn clothes left by their owners at the tailor and to determine the practice of buying and selling sewn clothes left by their owners at the tailor. This study uses an empirical legal method and is a type of field study research, data collection techniques used by means of observation, interviews and documentation as well as library data. In the perspective of Islamic economic law, the cloth handed over to the tailor and the sewing results remain the legal property of the customer, while the tailor only acts as a party providing services (ijarah contract) and a trustee for the goods (wadi'ah). Therefore, the original law is that it is haram or not permissible for the tailor to sell the clothes without the owner's explicit permission, because it is an act of selling someone else's property without rights, which in Islam is known as ghasb and violates the principle of justice. However, in conditions of hajah (urgent need), sharia law provides leniency. If the owner cannot be contacted, has been waited for a reasonable time, and the tailor has suffered a real loss due to the accumulation of the goods, then it is permissible to sell the goods with certain conditions.